Autoregulated resistance training: Does velocity-based training represent the future? - Nevin, J. (Strength and Conditioning Journal, 2019)
Traditionally, resistance training intensity has been based upon a percentage of an individual's 1rm. However, there are numerous shortcomings with this approach, including its failure to consider an athlete's conditional, day-to-day training readiness. In order to address these limitations, the use of various progressive auto-regulated resistance training protocols has been suggested in the literature. Recent advances in the monitoring of movement velocity offer a unique approach by which to optimize the use of auto-regulated resistance training. By matching established acute resistance training variables to specific movement velocities the strength and conditioning practitioner can optimize resistance training intensity and objectively identify the onset of neuromuscular fatigue.